Bacteria in agrobiology crop ecosystems - Maheshwari, Dinesh K.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. Bacteria in Agrobiology: Crop Ecosystems describes the beneficial role of plant growth promoting bacteria with special emphasis on oil yielding crops, cereals, fruits and vegetables. Chapters present studies on various aspects of bacteria-plant interactions, soil-borne and seed-borne diseases associated with food crops such as rice, sesame, peanuts, and horticultural crops. Further reviews describe technologies to produce inoculants, the biocontrol of post harvest pathogens as a suitable alternative to agrochemicals, and the restoration of degraded soils.
Maheshwari, DK: Sustainable Approaches for Biocontrol of Charcoal Rot and Fusarial wilt in sesame (Sesamum indicum L.) -- Johri, BN: Bacilli as PGPR in Crop Ecosystem -- Sa, T: Endophytic  Bacteria: Perspectives and Applications in Agricultural Crop Production -- Berg, G: PGPR interplay with rhizosphere communities and effect on plant health -- Roberts, DP: Impact of the complex nutritional environment in the spermosphere and rhizosphere on performance of Plant Growth-Promoting Rhizobacteria -- Karunaratne, A: Biocontrol mechanisms employed by PGPR and strategies of microbial antagonists in disease control on the postharvest environment of fruits- a comparative account -- Esitken, A: Use of plant growth promoting rhizobacteria (PGPR) in horticultural crops -- Reddy, MS: Prospects of PGPR for management of sheath blight of rice -- Yanni, YA: Beneficial Endophytic Rhizobia as Biofertilizer Inoculants for Rice -- Lugtenberg, BJJ: Microbial Control of plant root diseases -- Young, CC: Advanced technologies used in the studies of PGPR and the Application of Bioinoculants -- Saraf, M: Perspectives of PGPR as Biofertilizers in Agri-ecosystems -- Maheshwari, DK: Emerging role of Plant Growth Promoting Rhizobacteria in Agro- Industry -- Maheshwari, DK: Beneficial Interactions in Rhizosphere.
Electronic reproduction.
Keywords: Plant growth-promoting rhizobacteria; Host-bacteria relationships; Life sciences; Microbiology; Agriculture; Bacteriology; Plant breeding; Electronic books